Teachers’ and Learners’ Perceptions of Speaking Anxiety and Its Impact on Third-Year High School Students’ Speaking Performance: A Case Study at Soudani Mohamed Torki Secondary School, Sedrata - ALI Ilhem (My University, 2026)
Abstract This study explores teachers’ and learners’ perceptions of speaking anxiety and its impact on third-year high school students’ speaking performance at Soudani Mohamed Torki High School, Sedrata. It aims to identify the perceived sources and manifestations of speaking anxiety, examine its influ-ence on oral participation and performance, and suggest pedagogical practices that may help reduce its effects. The study adopted a convergent mixed-methods case study design combining quantita-tive and qualitative approaches. Data were collected through a students’ questionnaire, classroom observation, and semi-structured teacher interviews. The participants included 25 third-year high school students and three English teachers. Findings revealed that students experience a generally moderate level of speaking anxiety influenced by linguistic limitations, low self-confidence, fear of negative evaluation, and classroom-related factors. The results also showed that anxiety may affect fluency, participation, and willingness to communicate. Furthermore, triangulated findings indicated that supportive classroom environments, collaborative speaking activities, and encouraging teacher feedback may contribute to reducing anxiety and improving speaking performance. The study concludes that speaking anxiety is an important affective factor in EFL speaking performance and should be addressed through supportive pedagogical practices ---------------------------- الملخص تهدف هذه الدراسة إلى استكشاف تصورات المعلمين والمتعلمين حول قلق التحدث وأثره على الأداء الشفهي لدى تلاميذ السنة الثالثة ثانوي بثانوية سوداني محمد التركي بسدراتة، مع التركيز على مصادر هذا القلق ومظاهره وتأثيره على المشاركة الشفوية والأداء اللغوي، واقتراح ممارسات تربوية تساعد على الحد من آثاره. اعتمدت الدراسة تصميم دراسة حالة قائمًا على المنهج المختلط المتقارب، جامعًا بين البيانات الكمية والنوعية. وتم جمع المعطيات من خلال استبيان موجّه للتلاميذ، والملاحظة الصفية، ومقابلات شبه موجهة مع ثلاثة أساتذة للغة الإنجليزية. وشملت العينة 25 تلميذًا من السنة الثالثة ثانوي وثلاثة أساتذة. أظهرت النتائج وجود مستوى متوسط عمومًا من قلق التحدث لدى التلاميذ، مرتبط بعوامل لغوية ونفسية وصفية مثل محدودية الرصيد اللغوي، ضعف الثقة بالنفس، الخوف من التقييم السلبي، وبعض العوامل المرتبطة ببيئة القسم. كما بينت النتائج أن القلق قد يؤثر على الطلاقة والمشاركة والاستعداد للتواصل. وأظهرت نتائج التثليث أن البيئة الصفية الداعمة، والأنشطة التعاونية، والتغذية الراجعة المشجعة يمكن أن تسهم في تقليل القلق وتحسين الأداء الشفهي. -------------------------- Résumé Cette étude explore les perceptions des enseignants et des apprenants concernant l’anxiété de prise de parole et son impact sur la performance orale des élèves de troisième année secondaire au lycée Soudani Mohamed Torki à Sedrata. Elle vise à identifier les sources et manifestations perçues de cette anxiété, examiner son influence sur la participation orale et proposer des pratiques pédago-giques susceptibles d’en réduire les effets. L’étude adopte une approche d’étude de cas à méthodes mixtes convergentes, combinant des données quantitatives et qualitatives. Les données ont été re-cueillies au moyen d’un questionnaire destiné aux élèves, d’observations de classe et d’entretiens semi-directifs avec trois enseignants d’anglais. L’échantillon comprend 25 élèves et trois ensei-gnants. Les résultats montrent un niveau généralement modéré d’anxiété orale influencé par des li-mites linguistiques, un manque de confiance, la peur de l’évaluation négative et certains facteurs liés à la classe. Ils révèlent également que cette anxiété peut affecter la fluidité, la participation et la volonté de communiquer. La triangulation indique qu’un climat de classe favorable, les activités collaboratives et les rétroactions encourageantes peuvent réduire l’anxiété et améliorer la perfor-mance orale.
Keywords: speaking anxiety; speaking performance; EFL learners; teachers’ perceptions; mixed methods.; قلق التحدث، الأداء الشفهي، متعلمو الإنجليزية، تصورات المعلمين، المنهج المختلط; anxiété orale; performance orale; apprenants EFL; perceptions des enseignants; méthodes mixtes